Research progress in composition and function of hyperaccumulator-associated endogenous microorganism community - LUO Jipeng; TAO Qi; WU Keren; LI Tingqiang (浙江大学学报. 农业与生命科学版)
The endophytic microbiota of hyperaccumulators is capable of tolerating high concentration of heavy metals, and its composition and diversity markedly vary with host plant species, soil and pollutant types, etc. Hyperaccumulator-associated endophytic microbiota has been reported to promote host plant growth by producing phytohormones, inhibiting ethylene production, increasing macro and micro nutrients and enhancing plant’s resistance to abiotic stress. On the one hand, endophytic microbiota can increase solubility and bioavailability of heavy metals by releasing of protons, carboxylic acid anions, bacterial siderophores and other chelators. On the other hand, the promotion of root growth and the formation of symbiosis mycorrhizae can increase the uptake of heavy metals by root. In addition, other processes such as redox, biosorption and bioaccumulation mediated by endophytic microbiota can also influence the uptake of heavy metals. In terms of application, endogenous microorganism of hyperaccumulator has good application prospects in strengthening phytoremediation, improving crop yield and biofortification of trace elements. In this paper, we reviewed the community composition and succession rule of endophytic microorganism in hyperaccumulator, as well as the mechanism of promoting plant growth, heavy metal activation and uptake, and its application in agricultural production. Based on that, the future research emphasis is put forward.